Physical properties of bioplastic agar/chitosan blend. Issue 1 (1st February 2022) - Agusman,; Fransiska, D; Murdinah,; Wahyuni, T; Irianto, H E; Priambudi, P; Fateha,; Abdullah, A H D; Nissa, R D; Firdiana, B; Nurhayati,
Abstract: Thermoplastic agar/chitosan blend was prepared by a rheomix process, and the effect of concentration agar: chitosan on the material properties forms were investigated. This research aimed to observe the physical properties of bioplastic agar/chitosan produced through rheomix. Bioplastic was produced by mixing 65 % solid material (agar: chitosan) and 35% glycerol, the ration through the melting process at an initial temperature of 100°C. The weight ratio of agar : chitosan was 65% : 0% (F0/control), 52% : 13% (F1), 39 % : 26% (F2), 26 %: 39% (F3). The tensile strength and elongation of bioplastic were decrees with a higher chitosan concentration. The color and the opacity of bioplastic were affected by the ratio of agar: chitosan. The moisture content and the water vapor transmission rate (WVTR) of bioplastic were increased by increasing the chitosan ratio. The SEM micrograph of bioplastic showed that the blend agar and chitosan seem to have a rough and inhomogeneous surface than pure bioplastic agar. The best blend was bioplastic with agar: chitosan 52%: 13% (F1), which have properties of : tensile strength 4.95 ± 0.56 MPa, elongation at break 34.94 ± 0.99 %, moisture content 15.33 ± 0.43%, WVTR 3259.39 ± 28.12 g/m2.24 h.